Titanium ion doped V2O5 nanowire film and preparation method and application thereof
Through multiple coating and heating treatments, a titanium ion-doped V2O5 nanowire film was prepared, which solved the problems of film unevenness and poor electrochromic performance, and achieved uniformity and high cyclic stability.
Patent Information
- Application Number
- CN202510210261.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-04-15
AI Technical Summary
In the prior art, when preparing titanium ion-doped V2O5 films, the film thickness distribution is easily unevenly due to high hydrolysis activity, and when using a conductive substrate, the precursor solution cannot adhere uniformly, resulting in the inhomogeneity of the film and affecting the electrochromic performance.
By mixing the vanadium compound with the first solvent and mixing the titanium compound with the second solvent, forming a precursor solution, undergoing multiple coatings and heating treatments, and finally calcined at high temperatures, a titanium ion-doped V2O5 nanowire film was prepared.
The uniformity of the film and good electrochromic properties are achieved, the introduction of impurity ions is avoided, and the stability of electrochromic circulation is improved.
Smart Images

Figure CN119822827A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of inorganic non-metallic materials, and in particular to a titanium ion-doped V2O5 nanowire film and a preparation method and application thereof. Background Art
[0002] One of the common methods for preparing titanium ion-doped V2O5 thin films is the spin coating method. In the spin coating preparation process, a solution formed by an organic solvent such as a metal salt is often used to adjust the spin coating process and then calcine to obtain the film. However, due to the high hydrolysis activity of most metal salts, rapid hydrolysis will occur during the spin coating process, resulting in uneven thickness distribution of the film. In particular, when a conductive substrate (such as ITO conductive glass) is used, due to the low hydrophilicity and high surface tension of ITO, the precursor solution cannot be evenly attached to the substrate surface, which exacerbates the uneven distribution of the film, and this phenomenon will become more obvious with subsequent calcination.
[0003] Conventional solutions generally involve adding surfactants to precisely control the hydrolysis process of metal alkoxides or modifying the ITO surface. When adding surfactants, it is necessary to select them according to the characteristics of metal alkoxides, which are divided into ionic surfactants and non-ionic surfactants. When using ionic surfactants, impurities will be introduced into the film during subsequent calcination, resulting in performance degradation. When using non-ionic surfactants, the dosage is relatively large, resulting in the formation of a discontinuous island-shaped particle film, which will reduce the effective contact surface between the electrode and the electrolyte when applied to lithium-ion battery electrodes, resulting in performance degradation. Conventional ITO modification uses organic surfactants or silane coupling agents. When using silane coupling agents, subsequent calcination will bring silicon oxide residues and affect the electrochromic performance. When using organic surfactants, the gas generated by decomposition during the calcination process causes pores and unevenness in the upper film, and may even cause cracking.
[0004] Therefore, it is very necessary to achieve the preparation of uniform thin films without introducing impurity ions. Summary of the invention
[0005] The purpose of the present invention is to provide a titanium ion doped V2O5 nanowire film and a preparation method and application thereof, so as to achieve uniformity and good electrochromic performance of the film without introducing impurity ions.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a titanium ion-doped V2O5 nanowire film, comprising the following steps:
[0008] mixing a vanadium compound with a first solvent to obtain a vanadium compound solution;
[0009] mixing a titanium compound with a second solvent to obtain a titanium compound solution;
[0010] mixing the vanadium compound solution and the titanium compound solution to obtain a precursor solution;
[0011] After the precursor solution is first coated on a substrate, a first heating treatment is performed to obtain an intermediate product film;
[0012] Performing a second coating on the intermediate product film to obtain a composite film;
[0013] Alternatively, the steps of the third coating and the second heating treatment are sequentially repeated on the intermediate product film to obtain a composite film;
[0014] The composite film is calcined to obtain a titanium ion-doped V2O5 nanowire film.
[0015] Preferably, the vanadium compound includes one or more of tripropoxide vanadium oxide, vanadium chloride and bis(acetylacetonate)oxyvanadium, and the first solvent includes one or more of ethanol, isopropanol and n-butanol; the ratio of the molar number of the vanadium compound to the volume of the first solvent is 0.5 to 10 mol:10L.
[0016] Preferably, the titanium compound includes one or more of butyl titanate, titanium chloride and titanium isopropoxide, the second solvent includes acetylacetone and an organic solvent, the ratio of the mole number of acetylacetone to the volume of the organic solvent is 0.1 to 5 mol:8L, and the organic solvent includes ethanol, isopropanol or n-butanol; the ratio of the mole number of the titanium compound to the volume of the second solvent is 0.1 to 20 mol:8L.
[0017] Preferably, the volume ratio of the vanadium compound solution to the titanium compound solution is 10:0.05-5.
[0018] Preferably, the number of times of the first coating is 1 to 6 times, the rotation speed of each coating is independently 500 to 2000 rpm, the interval time of each coating is independently 10 to 60 s, the time of each coating is independently 20 to 80 s, and the dripping amount of the precursor solution is independently 0.01 to 0.1 mL during each coating; the temperature of the first heat treatment is 25 to 500°C, and the time is 5 to 120 min.
[0019] Preferably, the second coating is performed 1 to 6 times, the rotation speed of each coating is independently 500 to 2000 rpm, the interval time of each coating is independently 10 to 60 s, the time of each coating is independently 20 to 80 s, and the dripping amount of the precursor solution is independently 0.01 to 0.1 mL during each coating.
[0020] Preferably, the number of repetitions is 1 to 5 times; the number of the third coating is 1 to 6 times, the rotation speed of each coating is independently 500 to 2000 rpm, the interval time of each coating is independently 10 to 60 s, the time of each coating is independently 20 to 80 s, and the dripping amount of the precursor solution is independently 0.01 to 0.1 mL during each coating; the temperature of the second heat treatment is 25 to 500°C, and the time is 5 to 120 min.
[0021] Preferably, the calcination temperature is 300-500° C. and the calcination time is 2-10 hours.
[0022] The invention provides a titanium ion-doped V2O5 nanowire film prepared by the preparation method.
[0023] The present invention also provides the application of the titanium ion doped V2O5 nanowire film in an electrochromic device.
[0024] Beneficial effects of the present invention:
[0025] The present invention obtains vanadium compound solution and titanium compound solution respectively, and coats the precursor solution formed by mixing the two on the surface of the substrate to form a liquid surface layer, then performs heating treatment, and finally performs calcination to obtain a titanium ion-doped V2O5 nanowire film.
[0026] The present invention performs appropriate heating treatment on the liquid surface layer formed after coating, which helps to accelerate the volatilization of the liquid surface layer, promotes the rapid hydrolysis of the precursor, reduces the aggregation of droplets on the liquid surface layer, and avoids the phenomenon that the hydrolyzed precursor is left in situ due to the slow volatilization of the droplets to form a patchy film. The vanadium-titanium precursor is directly combined with the ITO substrate to form an oligomer, and grows into amorphous nanoparticles. In the subsequent calcination process, a nanowire film is obtained, which improves the uniformity of the titanium ion-doped V2O5 nanowire film, and also enhances the electrochromic cycle stability, effectively improving the electrochromic cycle performance of the traditional V2O5 nanowire film. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is Ti of Example 1 4+ -Optical photos of V2O5 nanowire film and comparative example 1 sample: Figure 1 (a) is Ti of Example 1 4+ -Optical photograph of V2O5 nanowire film, Figure 1 (b) is an optical photograph of the sample of Comparative Example 1;
[0028] Figure 2 is Ti of Example 2 4+ - SEM images of V2O5 nanowire film and comparative example 2 sample, where Figure 2 (a) is Ti of Example 24+ -SEM image of V2O5 nanowire film, Figure 2 (b) is the SEM image of the sample of Comparative Example 2;
[0029] Figure 3 is Ti of Example 3 4+ -Electrochromic cycle stability results of V2O5 nanowire film and comparative example 2 samples, where Figure 3 (a) is Ti of Example 3 4+ - Cyclic stability results of V2O5 nanowire films, Figure 3 (b) is the cyclic stability result of the sample in comparative example 2. DETAILED DESCRIPTION
[0030] The present invention provides a method for preparing a titanium ion-doped V2O5 nanowire film, comprising the following steps:
[0031] mixing a vanadium compound with a first solvent to obtain a vanadium compound solution;
[0032] mixing a titanium compound with a second solvent to obtain a titanium compound solution;
[0033] mixing the vanadium compound solution and the titanium compound solution to obtain a precursor solution;
[0034] After the precursor solution is first coated on a substrate, a first heating treatment is performed to obtain an intermediate product film;
[0035] Performing a second coating on the intermediate product film to obtain a composite film;
[0036] Alternatively, the steps of the third coating and the second heating treatment are sequentially repeated on the intermediate product film to obtain a composite film;
[0037] The composite film is calcined to obtain a titanium ion-doped V2O5 nanowire film.
[0038] In the present invention, unless otherwise specified, the required raw materials for preparation are all commercially available products well known to those skilled in the art.
[0039] In the present invention, the vanadium compound is preferably dissolved in the first solvent to obtain a vanadium compound solution.
[0040] In the present invention, the vanadium compound preferably includes one or more of vanadium oxide tripropoxide, vanadium chloride and bis(acetylacetonate)oxyvanadium, and further preferably includes vanadium oxide tripropoxide or vanadium chloride; the first solvent preferably includes one or more of ethanol, isopropanol and n-butanol, and further preferably includes isopropanol.
[0041] In the present invention, the ratio of the molar number of the vanadium compound to the volume of the first solvent is preferably 0.5 to 10 mol:10 L, more preferably 1 to 2.5 mol:10 L, and even more preferably 1.0 to 1.3 mol:10 L.
[0042] In the present invention, the titanium compound is preferably dissolved in the second solvent to obtain a titanium compound solution.
[0043] In the present invention, the titanium compound preferably includes one or more of butyl titanate, titanium chloride and titanium isopropoxide, and further preferably includes titanium isopropoxide.
[0044] In the present invention, the second solvent preferably includes acetylacetone and an organic solvent, and the ratio of the molar number of acetylacetone to the volume of the organic solvent is preferably 0.1-5 mol:8L, further preferably 0.2-1 mol:8L, and more preferably 0.4-0.5 mol:8L; acetylacetone is added to the system as a complexing agent to alleviate the hydrolysis process of vanadium compounds and titanium compounds.
[0045] In the present invention, the organic solvent includes ethanol, isopropanol or n-butanol, and more preferably includes isopropanol; the ratio of the molar number of the titanium compound to the volume of the second solvent is preferably 0.1-20 mol:8L, more preferably 1-12 mol:8L, and more preferably 2-9.6 mol:8L.
[0046] In the present invention, the vanadium compound solution and the titanium compound solution are preferably mixed uniformly to obtain a precursor solution; in the present invention, the volume ratio of the vanadium compound solution to the titanium compound solution is preferably 10:0.05-5, more preferably 10:0.1-5, and more preferably 10:0.2-5.
[0047] In the present invention, the precursor solution is preferably first coated on the substrate and then subjected to a first heating treatment to obtain an intermediate product film.
[0048] In the present invention, the number of the first coating is preferably 1 to 6 times, and further independently preferably 3 to 6 times; the rotation speed of each coating is independently preferably 500 to 2000 rpm, and further independently preferably 1000 to 1200 rpm, the interval time of each coating is independently preferably 10 to 60 s, and further independently preferably 30 s, the time of each coating is independently preferably 20 to 80 s, and further independently preferably 30 s, and the dripping amount of the precursor solution during each coating is independently preferably 0.01 to 0.1 mL, and further independently preferably 0.036 to 0.04 mL.
[0049] In the present invention, the substrate preferably comprises ITO glass.
[0050] In the present invention, the temperature of the heat treatment is preferably 25 to 500° C., more preferably 250 to 500° C., and the time is preferably 5 to 120 min, more preferably 30 to 60 min.
[0051] In the present invention, the intermediate product film is preferably subjected to a second coating to obtain a composite film; or, the intermediate product film is subjected to a third coating and a second heating treatment to obtain a composite film.
[0052] In the present invention, the number of the second coating is preferably 1 to 6 times, and further independently preferably 3 to 6 times; the rotation speed of each coating is independently preferably 500 to 2000 rpm, and further independently preferably 1000 to 1200 rpm, the interval time of each coating is independently preferably 10 to 60 s, and further independently preferably 30 s, the time of each coating is independently preferably 20 to 80 s, and further independently preferably 30 s, and the dripping amount of the precursor solution during each coating is independently preferably 0.01 to 0.1 mL, and further independently preferably 0.036 to 0.04 mL.
[0053] In the present invention, the number of repetitions is preferably 1 to 5 times, and more preferably 2 to 5 times; the number of the third coating is preferably 1 to 6 times, and further independently preferably 3 to 6 times; the rotation speed of each coating is independently preferably 500 to 2000 rpm, and further independently preferably 1000 to 1200 rpm, the interval time of each coating is independently preferably 10 to 60 s, and further independently preferably 30 s, the time of each coating is independently preferably 20 to 80 s, and further independently preferably 30 s, and the dripping amount of the precursor solution during each coating is independently preferably 0.01 to 0.1 mL, and further independently preferably 0.036 to 0.04 mL; the temperature of the second heat treatment is preferably 25 to 500°C, and further preferably 250 to 500°C, and the time is preferably 5 to 120 min, and further preferably 30 to 60 min.
[0054] In the present invention, the calcination temperature is preferably 300 to 500° C., more preferably 350 to 450° C., and the calcination time is preferably 2 to 10 hours, more preferably 2 to 6 hours.
[0055] The present invention preferably calcines the composite film to obtain a titanium ion-doped V2O5 nanowire film.
[0056] The present invention provides a titanium ion-doped V2O5 nanowire film prepared by the above preparation method, wherein the titanium ions are doped in a +4 valence state.
[0057] The present invention also provides the application of the titanium ion doped V2O5 nanowire film in an electrochromic device.
[0058] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0059] Example 1
[0060] Dissolve 0.3 mL of vanadium oxide tripropoxide in 10 mL of isopropanol, with the ratio of the mole of vanadium oxide tripropoxide to the volume of the isopropanol solution being 1.3 mol:10 L, to obtain a vanadium compound solution;
[0061] Dissolve 0.6 mL of titanium isopropoxide in 8 mL of acetylacetone-isopropanol solution (the ratio of the mole of acetylacetone to the volume of isopropanol is 0.5 mol:8 L), the ratio of the mole of titanium isopropoxide to the volume of the acetylacetone-isopropanol solution is 9.6 mol:8 L, to obtain a titanium compound solution;
[0062] 10 mL of the vanadium compound solution and 0.2 mL of the titanium compound solution were mixed evenly to obtain a precursor solution;
[0063] The precursor solution was first coated on the ITO glass at a rotation speed of 1000 rpm, the number of first coatings was 3 times, the interval time of each coating was 30 seconds, the time of each coating was 20 seconds, and the drop amount of the precursor solution was 0.03 mL independently during each coating. Then, the precursor solution was treated at 250° C. for 30 minutes for heating treatment to obtain an intermediate product film;
[0064] Repeat the third coating and the second heating treatment steps 4 times for the intermediate product film, the third coating is performed 3 times, the rotation speed of each coating is 1000 rpm, the interval time of each coating is 30 s, the time of each coating is 20 s, the drop amount of the precursor solution is 0.03 mL each time, the temperature of the second heating treatment is 250 ° C, and the time is 30 min to obtain a composite film;
[0065] The composite film was calcined at 450 °C for 2 h to obtain Ti 4+ -V2O5 nanowire film.
[0066] Example 2
[0067] The only difference from Example 1 is:
[0068] After the intermediate product film is prepared, the third coating and the second heating treatment steps are repeated twice on the intermediate product film to obtain a composite film;
[0069] The composite film was calcined at 450 °C for 2 h to obtain Ti 4+ -V2O5 nanowire film.
[0070] Example 3
[0071] The only difference from Example 1 is:
[0072] After the intermediate product film is prepared, the intermediate product film is subjected to a second coating, the number of the second coating is 6 times, the interval time of each coating is 30 seconds, the spin coating time of each coating is 30 seconds, the drop amount of the precursor solution during each coating is 0.036 mL, and the film is treated at 250° C. for 30 minutes for heating to obtain a composite film;
[0073] The composite film was calcined at 450 °C for 2 h to obtain Ti 4+ -V2O5 nanowire film.
[0074] Comparative Example 1
[0075] The only difference from Example 1 is:
[0076] After the precursor solution is prepared, the precursor solution is directly coated on the ITO glass at a rotation speed of 1000 rpm for 15 times to obtain a composite film;
[0077] The composite film was calcined at 450° C. for 2 h to obtain a comparative example 1 sample.
[0078] Comparative Example 2
[0079] The difference from Example 1 is:
[0080] After the precursor solution is prepared, the precursor solution is directly coated on the ITO glass at a rotation speed of 1000 rpm for 9 times to obtain a composite film;
[0081] The composite film was calcined at 450° C. for 2 h to obtain a comparative example 2 sample.
[0082] Characterization and performance determination
[0083] 1. The Ti of Example 1 4+ -V2O5 nanowire film and comparative example 1 sample were optically photographed, and the results are shown in Figure 1 , Figure 1 (a) is Ti of Example 1 4+ -Optical photograph of V2O5 nanowire film, Figure 1 (b) is an optical photograph of the sample of Comparative Example 1.
[0084] like Figure 1 As shown in (a), the sample after heat treatment and then spin coating has good uniformity, and the film layer has uniform color and is orange; Figure 1 As shown in (b), the sample directly spin-coated 15 times has uneven color and contains white and yellow patches.
[0085] 2. The Ti of Example 2 4+ -V2O5 nanowire film and comparative example 2 sample were observed by SEM. The results are shown in Figure 2 , Figure 2 (a) is Ti of Example 2 4+ -SEM image of V2O5 nanowire film, Figure 2 (b) is the SEM image of the sample of Comparative Example 2.
[0086] Compare Figure 2 (a) and Figure 2 In (b), it can be found that the nanowires of the comparative example 2 sample obtained without heating are unevenly distributed and the nanowire morphology is inconsistent, with nanobelts (left side, red arrow), nanowires (middle) and nanorods (right side, green arrow) respectively existing; while the sample of embodiment 2 obtained after heating shows that the nanowires are evenly distributed and of uniform size.
[0087] 3. The Ti of Example 3 4+ -V2O5 nanowire film and comparative example 2 samples were subjected to electrochromic cycle stability test according to the following method. The results are shown in Figure 3 , Figure 3 (a) is Ti of Example 3 4+ - Cyclic stability results of V2O5 nanowire films, Figure 3 (b) is the cyclic stability result of the sample of Comparative Example 2;
[0088] method:
[0089] 1) Preparation: First, the obtained film is prepared into an electrochromic device, that is, the obtained film is used as a working electrode, a blank ITO glass is used as a counter electrode, and a 0.5M LiClO4 / propylene carbonate solution is used as an electrolyte, and an electrochromic device is obtained by encapsulation;
[0090] 2) Test: The test was conducted using a UV-visible spectrophotometer in conjunction with an electrochemical workstation at a wavelength of 400 nm. The voltage was alternately applied for 104 times at a square wave voltage of -3.0 V and +3.0 V for 30 seconds each time.
[0091] like Figure 3 As shown in (a), the sample that was heat treated and then spin-coated decays slowly over time; Figure 3 As shown in (b), the sample directly spin-coated 9 times at room temperature decays rapidly, which indicates that heating treatment improves the uniformity of the film while also enhancing the cycle stability.
[0092] 4. Ti obtained in Example 3 4+ -V2O5 nanowire film and comparative example 2 sample were subjected to 103 electrochromic cycles respectively, and the optical comparison data before and after the cycles are shown in Table 1.
[0093] Table 1 Ti of Example 3 4+ - Optical comparison data of V2O5 nanowire film and comparative example 2 sample before and after electrochromic cycling
[0094] Optical contrast (%) Lap 3 Lap 102 Optical contrast change rate Example 3 14.8 4.4 29.73 Comparative Example 2 22.1 4.3 19.46
[0095] In Table 1, the optical contrast change rate is used to characterize the cycle stability, which is equal to the ratio of the optical contrast value of the 102nd cycle to the optical contrast value of the 3rd cycle (expressed as a percentage). It reflects the performance stability after the cycle. The higher the value, the better the cycle stability.
[0096] As shown in Table 1, the optical contrast change rate of the heated sample reaches 29.73%, which is 1.5 times that of the unheated sample (19.46%), and has higher cycle stability.
[0097] It can be seen from the above embodiments and comparative examples that the present invention provides a titanium ion-doped V2O5 nanowire film, and the obtained nanowire film has good uniformity, uniform film color, and good electrochromic cycle stability.
[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a titanium ion-doped V2O5 nanowire film, characterized in that: The following steps are involved: mixing a vanadium compound with a first solvent to obtain a vanadium compound solution; mixing a titanium compound with a second solvent to obtain a titanium compound solution; mixing the vanadium compound solution and the titanium compound solution to obtain a precursor solution; After the precursor solution is first coated on a substrate, a first heating treatment is performed to obtain an intermediate product film; Performing a second coating on the intermediate product film to obtain a composite film; Alternatively, the steps of the third coating and the second heating treatment are sequentially repeated on the intermediate product film to obtain a composite film; The composite film is calcined to obtain a titanium ion-doped V2O5 nanowire film.
2. The preparation method according to claim 1, characterized in that: The vanadium compound includes one or more of tripropoxide vanadium, vanadium chloride and bis(acetylacetonate)oxyvanadium, and the first solvent includes one or more of ethanol, isopropanol and n-butanol; the ratio of the mole number of the vanadium compound to the volume of the first solvent is 0.5 to 10 mol:10L.
3. The preparation method according to claim 1, characterized in that: The titanium compound includes one or more of butyl titanate, titanium chloride and titanium isopropoxide, the second solvent includes acetylacetone and an organic solvent, the ratio of the mole number of acetylacetone to the volume of the organic solvent is 0.1 to 5 mol:8L, and the organic solvent includes ethanol, isopropanol or n-butanol; the ratio of the mole number of the titanium compound to the volume of the second solvent is 0.1 to 20 mol:8L.
4. The preparation method according to claim 1, characterized in that: The volume ratio of the vanadium compound solution to the titanium compound solution is 10:0.05-5.
5. The preparation method according to claim 1, characterized in that: The number of times of the first coating is 1 to 6 times, the rotation speed of each coating is independently 500 to 2000 rpm, the interval time of each coating is independently 10 to 60 s, the time of each coating is independently 20 to 80 s, and the dripping amount of the precursor solution is independently 0.01 to 0.1 mL during each coating; the temperature of the first heating treatment is 25 to 500° C., and the time is 5 to 120 min.
6. The preparation method according to claim 1, characterized in that: The second coating is performed 1 to 6 times, the rotation speed of each coating is independently 500 to 2000 rpm, the interval time of each coating is independently 10 to 60 s, the time of each coating is independently 20 to 80 s, and the dripping amount of the precursor solution is independently 0.01 to 0.1 mL during each coating.
7. The preparation method according to claim 1, characterized in that: The number of repetitions is 1 to 5 times; the number of the third coating is 1 to 6 times, the rotation speed of each coating is independently 500 to 2000 rpm, the interval time of each coating is independently 10 to 60 s, the time of each coating is independently 20 to 80 s, and the dripping amount of the precursor solution is independently 0.01 to 0.1 mL during each coating; the temperature of the second heat treatment is 25 to 500°C, and the time is 5 to 120 min.
8. The preparation method according to claim 1, characterized in that: The calcination temperature is 300-500° C. and the calcination time is 2-10 hours.
9. The titanium ion doped V2O5 nanowire film prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the titanium ion doped V2O5 nanowire film according to claim 9 in an electrochromic device.